2021
DOI: 10.1186/s12935-021-02053-0
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly methylated-differentially genes and pathways among Iranian patients with colorectal cancer

Abstract: Background Methylation plays an important role in colorectal cancer (CRC) pathogenesis. The goal of this study was to identify aberrantly differentially methylated genes (DMGs) and pathways through bioinformatics analysis among Iranian CRC patients using Methylation Next Generation Sequencing. Methods This study has integrated results of SureSelectXT Methyl-Seq Target with the potential key candidate genes and pathways in CRC. Six CRC and six sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(35 reference statements)
0
1
1
Order By: Relevance
“…The versatile web‐interactive servers featured a high expression of ZNF726 in all breast cancer subclasses. However, on the contrary, few recent studies based on online databases reported least expression of ZNF726 with a high level of methylation in colorectal cancer (CRC) identifying it as a prognosis‑associated gene for CRC 58,59 . While in this study, high ZNF726 expression correlated to a higher HR in breast cancer patients, which slightly hinted that ZNF726 could be a potential prognostic marker in breast cancer.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The versatile web‐interactive servers featured a high expression of ZNF726 in all breast cancer subclasses. However, on the contrary, few recent studies based on online databases reported least expression of ZNF726 with a high level of methylation in colorectal cancer (CRC) identifying it as a prognosis‑associated gene for CRC 58,59 . While in this study, high ZNF726 expression correlated to a higher HR in breast cancer patients, which slightly hinted that ZNF726 could be a potential prognostic marker in breast cancer.…”
Section: Discussioncontrasting
confidence: 79%
“…However, on the contrary, few recent studies based on online databases reported least expression of ZNF726 with a high level of methylation in colorectal cancer (CRC) identifying it as a prognosis-associated gene for CRC. 58,59 While in this study, high ZNF726 expression correlated to a higher HR in breast cancer patients, which slightly hinted that ZNF726 could be a potential prognostic marker in breast cancer. On further experimental validation, our data demonstrated an elevated ZNF726 transcript in the malignant breast tumor tissues than the benign.…”
Section: Discussionmentioning
confidence: 52%